Breast and ovarian cancer incidence in BRCA1-mutation carriers. Breast Cancer Linkage Consortium. - Easton, D F (1995)
Dominant predisposition to early-onset breast cancer and/or ovarian cancer in many families is known to be the result of germ-line mutations in a gene on chromosome 17q, known as BRCA1. In this paper we use data from families with evidence of linkage to BRCA1 to estimate the age-specific risks of breast and ovarian cancer in BRCA1-mutation carriers and to examine the variation in risk between and within families. Under the assumption of no heterogeneity of risk between families, BRCA1 is estimated to confer a breast cancer risk of 54% by age 60 years (95% confidence interval [CI] 27%-71%) and an ovarian cancer risk of 30% by age 60 years (95% CI 8%-47%). Similar lifetime-risk estimates are obtained by examining the risks of contralateral breast cancer and of ovarian cancer, in breast cancer cases in linked families. However, there is significant evidence of heterogeneity of risk between families; a much better fit to the data is obtained by assuming two BRCA1 alleles, one conferring a breast cancer risk of 62% and an ovarian cancer risk of 11% by age 60 years, the other conferring a breast cancer risk of 39% and an ovarian cancer risk of 42%, with the first allele representing 71% of all mutations (95% CI 55%-87%). There is no evidence of clustering of breast and ovarian cancer cases within families.